Recurrent Abdominal Pain in Children Attending Paediatrics OPD - Sailendra Kumar Yeluri (Asian Journal of Clinical Pediatrics and Neonatology, 2018)
Background: Recurrent abdominal pain (RAP) is common in children. One to two of every 10 children will experience it at some time. Children with recurrent abdominal pain are often anxious or depressed. The original definition of RAP, published in 1958, included both organic and functional pain. Subjects and Methods: This is prospective, descriptive and observational study conducted at Viswa Bharathi Medical College and General Hospital from September 2017 to May 2018 among 90 children with RAP. Patients of age group of 4 to 14 years attending the paediatric OPD of tertiary care teaching hospital was included in the study. Children with age less than 4 years and more than 14 years not meeting the criteria of RAP were excluded from the study. Children with organic causes of RAP have been treated according to corresponding reason. Results: Occurrence of abdominal pain every day in ORAP was 10 and 32 NORAP children, and once per week in organic ORAP was 3 and 14 NORAP children.  Duration of a pain episodes most of the day in ORAP was 11 and 21 NORAP children. Severe pain can see in 9 ORAP and 24 NORAP, and mild pain in 2 ORAP and 19 NORAP. Whereas, site of pain especially in periumbilical region in ORAP was 5 and 28 NORAP children, and lower abdomen pain in organic ORAP was 4 and 23 NORAP children. Moreover, 2 months duration of disease in ORAP was 17 and 3 NORAP children. In addition, presence of bloating in ORAP was 6 and 22 NORAP children, and absence of bloating in ORAP was 11 and 51 NORAP children. Presence of early satiety in in ORAP was 8 and 19 NORAP children, and absence of satiety in ORAP was 9 and 54 NORAP children.  Conclusion: Recurrent abdominal pain (RAP) in children with careful history and examination, clear explanation and follow-up and a commitment from parent and child to stop the condition limiting normal activities, good results are obtained for children without referral, drugs or extensive testing.